Effect of Coenzyme Q10 and transcutaneous electrical acupoint stimulation in assisted reproductive technology: a retrospective controlled study - Shanqin Qi; Qi Liang; Lixia Yang; Xueyuan Zhou; Kun Chen; Ji Wen (BMC, 2022)
Abstract Purpose To investigate the effects of coenzyme Q10 (CoQ10) and transcutaneous electrical acupoint stimulation (TEAS) pretreatment on pregnancy in patients with poor ovarian response (POR). Methods A total of 330 POR patients who were pretreated with CoQ10 or CoQ10 combined with TEAS before their in vitro fertilization/intracytoplasmic sperm injection and embryo transfer (IVF/ICSI-ET) cycles and who were not pretreated were selected and divided into CoQ10 group (group A, n = 110), CoQ10 + TEAS group (group B, n = 110) and control group (group C, n = 110). For patients with 2 or more transfer cycles, only the information of the first cycle was included. Ovarian function, response to gonadotropin (Gn) stimulation, and pregnancy outcomes of the three groups were compared in the IVF/ICSI-ET cycles. Results After pretreatment, basal FSH, total Gn dosage and duration were comparable among the three groups (all p-value > 0.05), basal E2 in group B decreased significantly compared with the control group (p = 0.022). Endometrial thickness on the human chorionic gonadotropin (hCG) day, antral follicle counts (AFC), the numbers of oocytes, metaphase II (MII) eggs and excellent embryos in the two pretreatment groups were significantly increased compared with group C (all p-value < 0.001), but the rates of MII oocytes, fertilization and excellent embryos had no apparent change. The endometrial thickness on the day of hCG, the numbers of MII eggs and excellent embryos in group B were higher than those in group A (p < 0.001; p = 0.020; p = 0.027; respectively). The embryo implantation rate (IR), clinical pregnancy rate (CPR) and live birth rate (LBR) in group B were significantly higher than those in group C (p = 0.022; p = 0.010; p = 0.019; respectively), but not significantly different from group A. Conclusion CoQ10 alone or in combination with TEAS are effective methods for IVF/ICSI-ET adjuvant therapy, which can significantly improve ovarian reactivity, increase the numbers of retrieved eggs and superior embryos, and improve endometrial receptivity. Adjuvant TEAS on the basis of CoQ10 can significantly enhance pregnancy rates, but CoQ10 alone failed to present such an obvious effect.